2018
DOI: 10.1038/s41467-018-07242-6
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging heterogeneity across multiple datasets increases cell-mixture deconvolution accuracy and reduces biological and technical biases

Abstract: In silico quantification of cell proportions from mixed-cell transcriptomics data (deconvolution) requires a reference expression matrix, called basis matrix. We hypothesize that matrices created using only healthy samples from a single microarray platform would introduce biological and technical biases in deconvolution. We show presence of such biases in two existing matrices, IRIS and LM22, irrespective of deconvolution method. Here, we present immunoStates, a basis matrix built using 6160 samples with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
185
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(192 citation statements)
references
References 27 publications
(50 reference statements)
4
185
0
Order By: Relevance
“…Cell-type deconvolution algorithms have recently been used with genome-wide RNA expression data to help identify changes in immune cell proportions in the blood that are associated with TB disease, prospective TB disease risk and treatment success (25,40). To identify immune cell populations that are associated with time since TB exposure in the GC6-74 study, we used the leukocyte expression signature matrix 'immunoStates' and linear regression to infer leukocyte proportions for each subject's sample (40). We found that the proportion of CD4+ α/β T cells was increased at 6 months vs. baseline time point in the Gambian and Ethiopian cohorts (P = 0.0079; linear mixed model; Figure 4A), but was not significantly changed at 18 months (P = 0.20 vs. baseline; linear mixed model, included South African cohort; Figure 4B).…”
Section: Time Since Tb Exposure In Humans Is Associated With Alteratimentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-type deconvolution algorithms have recently been used with genome-wide RNA expression data to help identify changes in immune cell proportions in the blood that are associated with TB disease, prospective TB disease risk and treatment success (25,40). To identify immune cell populations that are associated with time since TB exposure in the GC6-74 study, we used the leukocyte expression signature matrix 'immunoStates' and linear regression to infer leukocyte proportions for each subject's sample (40). We found that the proportion of CD4+ α/β T cells was increased at 6 months vs. baseline time point in the Gambian and Ethiopian cohorts (P = 0.0079; linear mixed model; Figure 4A), but was not significantly changed at 18 months (P = 0.20 vs. baseline; linear mixed model, included South African cohort; Figure 4B).…”
Section: Time Since Tb Exposure In Humans Is Associated With Alteratimentioning
confidence: 99%
“…Cell type proportions in blood were estimated from RNA-seq data as previously described using the R MetaIntegrator package (25,40,43). Gene-level expression for this deconvolution was obtained from the ARCHS 4 resource (61).…”
Section: Cell Type Deconvolution Pathway and Transcriptional Module mentioning
confidence: 99%
“…Cell subsets were identified using a "basis set" of published marker genes called immunoStates (71). The mean expression of each gene was computed for each cluster from the scaled log normalized expression values; each cluster was then assigned to the immunoState subset with the highest Pearson correlation value.…”
Section: Single-cell Library Preparation and Gene Expression Analysismentioning
confidence: 99%
“…Although examples exist of both general purpose immune signature matrices, e.g. LM22 (Newman et al, 2015) and Immunostates (Vallania et al, 2018), and more tissue specific ones e.g. M17 (Ciavarella et al, 2018), these matrices are most likely not appropriate for all diseases and tissue types.…”
Section: Introductionmentioning
confidence: 99%